Know your enemy, fight the outbreak: an Italian experience. (30th September 2020) - Cuccaro, C; Tarroni, M; Tinturini, A; Cresti, S; Basagni, C; Nante, N; Messina, G; De Marco, F M
Abstract: Issue: The New Delhi-Enterobateriaceae producing metallo-beta-lactamase NDM, resistant to carbapenems, are responsible of hospital outbreaks. The European Centre for disease prevention and control has published a report about the NDM outbreaks in Italy. Knowledge and application of all types of precautions is necessary to obtain adequate control. Description: Between June and August 2019 an outbreak of Klebsiella pneumoniae producing NDM-1 occurred in an acute cardiac surgery setting from medium to high intensity, in a third level-hospital in Italy. Every patient with at least one positive typing test for NDM in clinical specimens was defined as a case. The infection control team sought patient 0, reviewed patients' daily records and created a timeline to control movements, verifying risk factors and time to positivity. The correct application of isolation and standard precautions was assessed. Auditing and training sessions were carried out. Our aim is to verify if these actions sufficed to control and halt the outbreak. Results: Fourteen cases were identified, mean age=66.28 (SD = 13.55), 71.43% of them had a previous negative test. Positivity was found in samples from 13 rectal swabs (prevalence 12.38%), 7 lung aspirates, 3 urine cultures, 2 blood cultures and 2 wound swabs. Eight patients were positive in multiple body districts, 5 have been admitted to the same hospital within the year before, 3 came from other hospitals. The patient 0 has been moved in from a medical ward. After auditing, a training class was given to healthcare staff. The class concerned NDM phenotype, hand hygiene, isolation and personal protective equipment, with further observation in wards. In the following three months no new cases were registered. Lessons: A continuous high-level adherence to standard precautions and hand hygiene by healthcare staff should be supported by adequate training. This is confirmed to be a strong action to prevent or stop cross-contamination. Key messages: Colonization of multiresistant germs in healthcare due to cross-contamination has to be tackled promptly. Auditing and training actions should be taken into serious account in order to ensure an effective reaction from healthcare staff.